Disease and medicine in India : a historical overview - Indian History Congress. Session 2001 : Kolkata, India); Kumar, Deepak, 1952- ([Aligarh] : Indian History Congress ; New Delhi : Tulika, 2001)
Seminar papers presented at a special panel in 61st session of Indian History Congress held at Kolkata, 1-3 Jan. 2001.
Includes bibliographical references (p. 276-289) and index.
Keywords: Traditional medicine -- India -- Congresses; Herbs -- India -- Therapeutic use -- Congresses; Medicine popular -- India -- Congresses